The effects of hemodynamics on the inner layers of the aortic wall in patients with a bicuspid aortic valve. Issue 5 (2017) - Grewal, Nimrat; Girdauskas, Evaldas; DeRuiter, Marco C; Goumans, Marie-José; Lindeman, Jan H; Disha, Kushtrim; Wolterbeek, Ron; Schoor, Deborah IE; Klautz, Robert JM; Poelmann, Robert E; Groot, Adriana C Gittenberger-de
No abstract available